The life experiences of adolescent female students who use social media - Khairiyatul Munawwarah; Shelly Iskandar; Imas Rafiyah (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Social media is a place for students to follow trends. However, Islamic boarding schools limit students by prohibiting them from bringing cell phones; therefore, they are not influenced by the outside world, even online.Purpose: The purpose of this study is to explore the experiences of female students as users of social media related to dormitory rules.Methods: Using a qualitative research design with a phenomenological approach. The research was conducted by in-depth interviews with 8 female students at Madrasah Ulumul Qur'an Langsa aged 15-18 years. Interview transcripts were analyzed using the Colaizzi method.Results: Six themes emerged from this study including: students bring cell phones to boarding schools because of the influence of friends and want to see updates, the use of social media as entertainment in their spare time, social media affects the way students follow fashion, the influence of the outside environment is more dominant on the behavior of students than the media in social media. The values instilled in the pesantren become a bulwark in the face of the outside world, and students want to make the best use of social media.Conclusions: Female students want to make the best use of social media to atone for the violations committed. They also agree that the prohibition of bringing cell phones and access to social media in Islamic boarding schools is the right thing because it can cause negligence and jealousy in friends who do not carry cell phones.